Microglia: Immune Regulators of Neurodevelopment - Cowan, Maureen; Petri, William A. (Frontiers in Immunology, 2018)
Microglia, the tissue-resident macrophages of the central nervous system (CNS), have characterized roles in combating infection, clearing cellular debris, and maintaining tissue homeostasis. In addition to these typical immunological roles, microglia have been revealed to be active players in complex neurodevelopmental programs such as neurogenesis and synaptic pruning, during which they interact with neurons and macroglia to provide trophic support, respond to cytokine and metabolic signals derived from the local neural environment, and drive the refinement of functional neuronal circuits. Microglia appear to be developmentally regulated by the host microbiome, and have been shown to dynamically respond to metabolic products from gut microbiota in a sex-dependent manner. Due to their constant surveillance of the brain parenchyma, involvement in development, and salient reactivity to both peripheral immune and microbiome-derived signals, microglia may additionally serve as a key cellular intermediate linking neurodevelopmental disorders such as autism and schizophrenia with microbiota influences in models of maternal immune activation (MIA). This review examines both well-established and emerging literature and perspectives on microglia in the context of neurodevelopment, with a particular emphasis on the role of the host microbiome in influencing microglial function during health and disease states.